This is so provided that the velocity changes continuously in which case we can apply the mean value theorem.
<span>Velocity (v) is the derivative of displacement (x) : </span>
<span>v = dx/dt </span>
<span>Monk 1 arrives after a time t* and Monk 2 too. </span>
<span>Name v1(t) and v2(t) their respective velocities throughout the trajectory. </span>
<span>Then we know that both average velocities were equal : </span>
<span>avg1 = avg2 </span>
<span>and avg = integral ( v(t) , t:0->t*) / t* </span>
<span>so </span>
<span>integral (v1(t), t:0->t*) = integral (v2(t), t:0->t*) </span>
<span>which is the same of saying that the covered distances after t* seconds are the same </span>
<span>=> integral (v1(t) - v2(t) , t:0->t*) = 0 </span>
<span>Thus, name v#(t) = v1(t) - v2(t) , then we obtain </span>
<span>=> integral ( v#(t) , t:0->t*) = 0 </span>
<span>Name the analytical integral of v#(t) = V(t) , then we have </span>
<span>=> V(t*) - V(0) = 0 </span>
<span>=> V(t*) = V(0) </span>
<span>So there exist a c in [0, t*] so that </span>
<span>V'(c) = (V(t*) - V(0)) / (t* - 0) (mean value theorem) </span>
<span>We know that V(0) = V(t*) = 0 (covered distances equal at the start and finish), so we get </span>
<span>V'(c) = v#(c) = v1(c) - v2(c) = 0 </span>
<span>=> v1(c) = v2(c) </span>
<span>So there exist a point c in [0, t*] so that the velocity of monk 1 equals that of monk 2. </span>
(3x^2 - 2x)(x + 4)
<em><u>First step would be: distributive property.</u></em>
3x^3 + 12x^2 - 2x^2 - 8x
<em><u>Combine like terms.</u></em>
3x^3 + 10x^2 - 8x is the simplified form of the functions multiplied.
Your answer is D.
X - 10 = 25
add 10 to both sides
X = 35
Answer:
so for what I'm thinking is 2*5 for the amount of hours in a school week and then you get 10 then times that by 15 for the amount of weeks in a semester which is 150 then times that by 3 and you get 450 thats the simple way so if you are also studying over the weekend it would be 630 of a entire year
Step-by-step explanation in the answer
Answer: The number is: "2 " .
__________________________________________
Explanation:
__________________________________________
Write the expression; which is an equation, as follows:
__________________________________________
" 4x <span>− 12 = 2(-x) " ; in which "x" represents "the number for which we shall solve" .
___________________________________________
Note:
If the "number" = "x" ; the "opposite of the number" = " -x " ;
</span>___________________________________________
Rewrite as: " 4x <span>− 12 = -2x " ;
</span>_____________________________________________
→ Add "12" ; & add "2x" ; to EACH SIDE of the equation:
4x − 12 + 12 + 2x = -2x + 12 + 2x ;
to get: 6x = 12 ;
____________________________________________________
Now, divide each side of the equation by "6" ;
to isolate "x" on one side of the equation; & to solve for "x" ;
____________________________________________________
6x / 6 = 12 / 6 ;
to get: x = 2 .
____________________________________________________
Answer: The number is: "2 " .
____________________________________________________
Let us check our answer, by plugging in "2" for "x" in our original equation:
_____________________________________________________
→ " 4x − 12 = 2(-x) " ;
Let us plug in "2" for "x" ; to see if the equation holds true; that is; if both side of the equation are equal; when "x = 2" ;
→ " 4(2) − 12 = ? 2(-2) ??
→ 8 − 12 = ? -4 ? ;
→ -4 = ? -4 ?? Yes!
__________________________________________________